Application of a portable instrument for rapid and reliable detection of SARS‐CoV‐2 infection in any environment. (23rd April 2020) - Martinelli, Federico; Perrone, Anna; Della Noce, Isabella; Colombo, Lorenzo; Lo Priore, Stefano; Romano, Simone
Abstract: The ongoing outbreak of the novel coronavirus (SARS‐CoV‐2) infection is creating serious challenges for health laboratories that seek to identify viral infections as early as possible, optimally at the earliest appearance of symptom. Indeed, there is urgent need to develop and deploy robust diagnostic methodologies not only to use in health laboratory environments but also directly in places where humans circulate and spread the virus such as airports, trains, boats, and any public aggregation places. The success of a reliable and sensitive asymptomatic diagnosis relies on the identification and measurement of informative biomarkers from human host and virus in a rapid, sensitive, and inexpensive manner. The objective of this article is to describe an innovative multidisciplinary approach to develop an efficient, inexpensive, and easy‐to‐use portable instrument (bCUBE ® by Hyris Ltd) that can be employed as a surveillance system for the emergency caused by SARS‐CoV‐2. A solution for Coronavirus testing, compliant with CDC guidelines, is scheduled to be released in the next weeks. In addition, we will describe a workflow and path of an integrated multi‐omic approach that will lead to host and pathogen biomarker discovery in order to train the instrument to provide reliable results based on a specific biomarker's fingerprint of SARS‐CoV‐2 infection.